Menakar Kontradiksi Implementasi Teori Direct Teaching dan Indirect Teaching dalam Permendikbud No 37 Tahun 2018 - Arief, Mochamad Budi; Moh. Rodhi (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2020)
This article aims to describe the implementation of direct teaching and indirect teaching in Permendikbud No. 37 of 2018 which is not in line with the theory, especially indirect teaching. This research is a qualitative literature study to interpret the phenomena in the literature. The approach used is an empirical approach which is contrasted with an apriorist, rationalistic, or intellectualist orientation. Simultaneous qualitative analysis, each influencing all the others, then, comparisons are made between the different types of organizations to study the unit of analysis. Finally, the book's social artifacts become the unit of analysis. From the results of the discussion, it can be concluded as follows: 1) Indirect teaching strategies exemplify teaching concepts, patterns, and abstracts for inquiry, problem solving, and discovery learning experiences that encourage students to think beyond the facts given, conclude and make generalization as a result or a follow-up to direct instruction or direct learning, where the teacher focuses students' attention on a problem and then provides students with only background information. Contradictory to this, Permendikbud No. 37/2018 concerning amendments to Permendikbud No. 24/2016 on KI and KD Curriculum 2013 mentions the formulation of competency in spiritual attitudes, namely respecting and living up to the teachings of the religion it adheres to. The formulation of social attitude competence is showing honest behavior, discipline, responsibility, courtesy, care, and confidence in interacting with family, friends, teachers, and neighbors. Both competencies are achieved through indirect teaching, namely modeling, habituation, and school culture, by paying attention to the characteristics of subjects and the needs and conditions of students. 2) Indirect learning has the following characteristics: (1) Students are responsible for their own learning processes and outcomes; (2) students learn by absorbing and adapting new information into their cognitive structures with what they already know and believe from the learning process; and (3) students solve problems through active-collaborative discussions in Permendikbud No. 37 of 2018 concerning changes to Permendikbud No. 24 of 2016 concerning KI and KD Curriculum 2013 is very small and does not even touch the characteristics referred to.